The Transeunt Listener: Towards Futurities of Re-learning in Truth and Reconciliation Curriculum and Teacher Education - Phillips, Patrick (Journal of the Canadian Association for Curriculum Studies, 2025)
What does it mean to read, write and act towards reconciliation in curriculum and teacher education? To answer this question, I perform a situated literature review of Truth and Reconciliation teacher education research. I borrow from Lisa Farley’s (2010) concept of the reluctant pilgrim. While Farley reflects on a physical journey to understand how belief can withstand historical loss and immersion in ongoing systems of colonial power, I engage with her concept psychically; I attend to the words and listen for the implied hopes of the authors I read. Also attentive to my own beliefs and hopes as I read them, I become what I term a transeunt listener. I discuss how I became a transeunt listener through a form of reading-as-encounter and how it enabled me to understand how teacher education might address what I see as three tensions in truth and reconciliation teacher education discourse: 1) belonging; 2) disruption of settler consciousness; and 3) an expanded ethical capacity in teachers and curriculum theorists.